Exhaled nitric oxide levels and blood eosinophil counts independently associate with wheeze and asthma events in National Health and Nutrition Examination Survey subjects - Malinovschi, Andrei; Fonseca, João A.; Jacinto, Tiago; Alving, Kjell; Janson, Christer (Journal of allergy and clinical immunology, 2013)
Fraction of exhaled nitric oxide (Feno) and blood eosinophil count (B-Eos) values, markers of local and systemic eosinophilic inflammation, respectively, are increased in asthmatic patients. Little is known about the relation of these markers to reported wheeze and asthma events in a random population sample. We sought to determine the individual and independent values of B-Eos and Feno in relation to wheeze, asthma diagnosis, and asthma events in a cross-sectional study. Feno and B-Eos values were measured in 12,408 subjects aged 6 to 80 years from the National Health and Nutrition Examination Survey 2007-2008 and 2009-2010. Current wheeze and asthma diagnosis, as well as asthma attacks and asthma-related emergency department (ED) visits within the last 12 months, were assessed by means of questionnaires. Intermediate or high Feno values and intermediate or high B-Eos values were independently associated with having asthma, wheeze, and asthma attacks. However, only intermediate and high B-Eos values were independently associated with asthma-related ED visits. High Feno (≥50 ppb) and B-Eos (≥500 cells/mm3) values rendered an adjusted odds ratio of 4.5 of having wheeze, 5.1 of having asthma, 5.4 for asthma attacks, and 2.9 for asthma-related ED visits compared with normal Feno (<25 ppb) and B-Eos (<300 cells/mm3) values. Exhaled nitric oxide and B-Eos values offered independent information in relation to the prevalence of wheeze, asthma diagnosis, and asthma events in this random population sample. The clinical importance of these findings in asthmatic patients with regard to phenotyping and individualized treatment, considering both local and systemic eosinophilic inflammation, needs to be determined.